Population Allocation in Resource-Based Economy Areas and Entrepreneurship Support - Bukharova, Evgenya; Vorontsova, Irina; Ferova, Irina; Vitkovskaya, Ludmila (Louvain-la-Neuve: European Regional Science Association (ERSA), 2014)
Russian President Vladimir Putin placed an emphasis on priority development of the resource regions of Eastern Siberia: this is related to the large-scale development of natural resources and to the development of modern manufacturing industries. In this context, it is necessary to solve the problem of rational territorial distribution of new industries, taking into account the current territorial structure. ? The present stage of the new industrialization in Siberian regions will be accompanied by stiff competition for human capital on the background of the increasing role of human capital in today's economy. ? The system of focal allocation of population in resource regions with a significant differentiation of living and business conditions, which was established in previous years, usually does not coincide with the future allocation scheme. In the Krasnoyarsk Krai alone large investment projects will lead to increasing the share of the Krasnoyarsk Krai's territories, actively involved in economic development. ? Imperfect mechanisms for institutional support of business in the regions and forms of territorial organization of production limit the investment attractiveness of the regions. The example of Krasnoyarsk Krai was taken as a regional model for conducting the analysis of influence factors and proposing approaches to strategic development of territorial settlement patterns: ? Core settlements - small towns are "points of growth" in new places of concentration of economic activity in which investment projects stimulate the economic development of the territory. ? The formation of an optimal backbone for the population allocation system in these areas will require the use of intra-regional shift work, which will facilitate the involvement of working population of the already existing settlements of the Krai into economic activities. ? It is necessary to accelerate the process of formation of Krasnoyarsk agglomeration as a business center, which multifunctional environment and its integrative properties ...